Consistent Conditional Moment Closure Modelling of a Lifted Turbulent Jet Flame Using the Presumed β-PDF Approach. (19th May 2014) - El Sayed, Ahmad; Fraser, Roydon A.
Abstract : A liftedH 2 / N 2 turbulent jet flame issuing into a vitiated coflow is investigated using the conditional moment closure. The conditional velocity (CV) and the conditional scalar dissipation rate (CSDR) submodels are chosen such that they are fully consistent with the moments of the presumedβ probability density function (PDF). The CV is modelled using the PDF-gradient diffusion model. Two CSDR submodels based on the double integration of the homogeneous and inhomogeneous mixture fraction PDF transport equations are implemented. The effect of CSDR modelling is investigated over a range of coflow temperatures (T c ) and the stabilisation mechanism is determined from the analysis of the transport budgets and the history of radical build-up ahead of the stabilisation height. For allT c, the balance between chemistry, axial convection, and micromixing, and the absence of axial diffusion upstream of the stabilisation height indicate that the flame is stabilized by autoignition. This conclusion is confirmed from the rapid build-up ofH O 2 ahead ofH, O, andOH . The inhomogeneous CSDR modelling yields higher dissipation levels at the most reactive mixture fraction, which results in longer ignition delays and larger liftoff heights. The effect of the spurious sources arising from homogeneous modelling is found to be small but nonnegligible, mostly notably within the flame zone.